Identification of physicochemical properties that modulate nanoparticle aggregation in blood - Soddu, Ludovica (Beilstein J Nanotechnol, 2020)
Inorganic materials are receiving significant interest in medicine given their usefulness for therapeutic applications such as targeted drug delivery, active pharmaceutical carriers and medical imaging. However, poor knowledge of the side effects related to their use is an obstacle to clinical translation. For the development of molecular drugs, the concept of safe-by-design has become an efficient pharmaceutical strategy with the aim of reducing costs, which can also accelerate the translation into the market. In the case of materials, the application these approaches is hampered by poor knowledge of how the physical and chemical properties of the material trigger the biological response. Hemocompatibility is a crucial aspect to take into consideration for those materials that are intended for medical applications. The formation of nanoparticle agglomerates can cause severe side effects that may induce occlusion of blood vessels and thrombotic events. Additionally, nanoparticles can interfere with the coagulation cascade causing both pro- and anti-coagulant properties. There is contrasting evidence on how the physicochemical properties of the material modulate these effects. In this work, we developed two sets of tailored carbon and silica nanoparticles with three different diameters in the 100–500 nm range with the purpose of investigating the role of surface curvature and chemistry on platelet aggregation, activation and adhesion. Substantial differences were found in the composition of the protein corona depending on the chemical nature of the nanoparticles, while the surface curvature was found to play a minor role. On the other hand, large carbon nanoparticles (but not small carbon nanoparticles or silica nanoparticles) have a clear tendency to form aggregates both in plasma and blood. This effect was observed both in the presence or absence of platelets and was independent of platelet activation. Overall, the results presented herein suggest the existence of independent modes of action that are differently affected by the physicochemical properties of the materials, potentially leading to vessel occlusion and/or formation of thrombi in vivo.